A lady for all seasons - Alexander, T. J. (Vintage, a divison of Penguin Random House, 2026)
"It is a truth universally acknowledged that a woman who has lost her fortune must be in need (not want) of a husband. Beautiful, cunning Verbena Montrose must marry to save herself and her odious family from abject poverty. Fortunately, what she lacks in a dowry, she makes up for in the currency of gossip. When she hears an alarming rumor about her very dear, very queer friend Étienne that could ruin him, she comes to his aid with a proposal--for a marriage of convenience, that is. But when Verbena discovers that a mysterious and celebrated poet by the name of Flora Witcombe has been publishing verses that hint she is onto their scheme, Verbena has no choice but to pretend to be a poet herself to confront her in a local salon. And--unexpectedly--be charmed by her. Flora, in turn, is terrified by and smitten with Verbena in equal measure. But she holds a secret of her own: he is also William Forsyth, a struggling novelist and fifth son of a minor noble family. And if circumstances don't allow Flora to woo Verbena, perhaps William can. Faced with two suitors and a fiancé, Verbena, who has always had to be clever to survive in society, starts to realize she may need to think outside of society's constraints to find true happiness."--Amazon.